Measurement of CP asymmetries in D s + → η π + $$ D_{(s)}^{+}→ η π^{+} $$ and D s + → η ′ π + $$ D_{(s)}^{+}→ η^{′ }{π}^{+} $$ decays - The LHCb collaboration; R. Aaij; A. S. W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; B. Adeva; M. Adinolfi; H. Afsharnia; C. Agapopoulou; C. A. Aidala; S. Aiola; et al. (Journal of High Energy Physics, 2023)
Abstract Searches for CP violation in the decays D s + → η π + $$ {D}_{(s)}^{+}\to \eta {\pi}^{+} $$ and D s + → η ′ π + $$ {D}_{(s)}^{+}\to {\eta}^{\prime }{\pi}^{+} $$ are performed using pp collision data corresponding to 6 fb −1 of integrated luminosity collected by the LHCb experiment. The calibration channels D s + → ϕ π + $$ {D}_{(s)}^{+}\to \phi {\pi}^{+} $$ are used to remove production and detection asymmetries. The resulting CP-violating asymmetries are A CP = D + → η π + = 0.34 ± 0.66 ± 0.16 ± 0.05 % , A CP = D s + → η π + = 0.32 ± 0.51 ± 0.12 % , A CP = D + → η ′ π + = 0.49 ± 0.18 ± 0.06 ± 0.05 % , A CP = D s + → η ′ π + = 0.01 ± 0.12 ± 0.08 % , $$ {\displaystyle \begin{array}{l}{\mathcal{A}}^{CP}=\left({D}^{+}\to \eta {\pi}^{+}\right)=\left(0.34\pm 0.66\pm 0.16\pm 0.05\right)\%,\\ {}{\mathcal{A}}^{CP}=\left({D}_s^{+}\to \eta {\pi}^{+}\right)=\left(0.32\pm 0.51\pm 0.12\right)\%,\\ {}\begin{array}{l}{\mathcal{A}}^{CP}=\left({D}^{+}\to {\eta}^{\prime }{\pi}^{+}\right)=\left(0.49\pm 0.18\pm 0.06\pm 0.05\right)\%,\\ {}{\mathcal{A}}^{CP}=\left({D}_s^{+}\to {\eta}^{\prime }{\pi}^{+}\right)=\left(0.01\pm 0.12\pm 0.08\right)\%,\end{array}\end{array}} $$ where the first uncertainty is statistical, the second is systematic and the third, relevant for the D + channels, is due to the uncertainty on A CP = D + → ϕ π + $$ {\mathcal{A}}^{CP}=\left({D}^{+}\to \phi {\pi}^{+}\right) $$ . These measurements, currently the most precise for three of the four channels considered, are consistent with the absence of CP violation. A combination of these results with previous LHCb measurements is presented.